Simultaneous Bilateral Quadriceps Tendon Rupture following Long-Term Low-Dose Nasal Corticosteroid Application - Mohamed Omar; Philipp Haas; Max Ettinger; Christian Krettek; Maximilian Petri (Case Reports in Orthopedics)
Simultaneous bilateral quadriceps tendon rupture is a very rare injury, which was previously only described in slightly more than 100 cases in the English literature. Occurrence after minor trauma is predominantly associated with certain medical conditions including chronic diseases and long-term use of certain drugs. We report the case of a 61-year-old healthy patient who sustained a simultaneous bilateral quadriceps tendon rupture following minor trauma. Medical history was completely clear except of a long-term nasal corticosteroid medication due to allergic rhinitis.